Psychological Features of Raising a Child in the Family - Mansur qizi, Baxtiyorova Munira (European Journal of Life Safety and Stability (2660-9630), 2023)
information is given about the role of parents in the family, about the importance of family traditions and rituals in the upbringing of children, about the influence of the establishment of reading in the family on the upbringing of children.